STUDY THE EFFECT OF THE AQUATIC AND ALCOHOLIC EXTRACTS OF Peganum harmala SEEDS ON Entamoeba histolytica IN VITRO - Al-Shanawi, Fawzia; Al-Obaidi, Heba (Iraqi Journal of Science, 2024)
In vitro test has been made to find out the efficacy of aqueous and ethanolic extract of Peganum harmala seeds against Entamoeba histolytica in three concentrations (1000, 1500, 2000 μg/ml) in an exposure time of 2hrs, preliminary chemical analysis has been performed for some chemical groups which may exist in the seeds.Results showed that all concentrations of alcohol extracts caused high mortality against parasite by using the alcohol extract in all used concentrations, this may due to the high containing of alkaloids. The highest mortality percentage achieved by alcohol extract was 97.5% while it was 90.1% by aqueous extract at 2000 μg/ml.